Filtering information framework for textual based information / Bujang Kelana Azme Ajor - Ajor, Bujang Kelana Azme (Faculty of Information Technology and Quantitative Sciences, 2005)
Nowadays, information becomes the crucial asset to everybody. If someone tries to give irrelevant information, he or she will be charged or sued in court regarding on the abusive information. Adults can make decision about what information they want to give out, or what degree of tracking they want to allow in exchange for discounts or access to certain sites. Young children are not likely to understand the risks and trade-offs. This research will focus on the existing exchange board at the website which have applied filtering information such as Leaning-base filtering framework. Rule-base filtering framework, and Collaborative filtering fi^amework. As usual, there is much information that will be shared with many people. To ensure that the information which is published is suitable for people, filtering information framework is needed to filter out all the information to avoid inappropriate people getting the message or information. Abuse words are also being used widely at Internet. This is not good for children because they will be influenced to do some criminal or expose in social problem. In getting a great country, all these not need to happen. As solution, a filtering information framework is needed to be embedding at the exchange board. COPYRIGHT ©